To convert the equation \( y = -4(x + 5)^2 - 3 \) from vertex form to standard form, we will first expand the equation.
-
Start with the vertex form: \[ y = -4(x + 5)^2 - 3 \]
-
Expand \( (x + 5)^2 \): \[ (x + 5)^2 = x^2 + 10x + 25 \]
-
Substitute this back into the equation: \[ y = -4(x^2 + 10x + 25) - 3 \]
-
Distribute the \(-4\): \[ y = -4x^2 - 40x - 100 - 3 \]
-
Combine the constant terms: \[ y = -4x^2 - 40x - 103 \]
Thus, the standard form of the equation is: \[ \boxed{y = -4x^2 - 40x - 103} \]
This matches one of the given responses.